Interventions promoting adolescent girls' economic capabilities: what works? A rapid evidence review - Maria Stavropoulou (Overseas Development Institute (ODI), 2018)
Addressing adolescent girls' persistent economic disadvantage is the focus of multiple interventions for girls in low- and middle-income countries (LMICs) to reduce youth unemployment, poverty and vulnerability. While the importance of these interventions is well understood, what works to strengthen girls' economic capabilities is much less well known. This rapid evidence review focuses on evaluated interventions that target adolescent girls in LMICs with economic strategies that seek to promote their economic capabilities and empower them. The review examines 57 interventions, grouped into three categories: interventions providing financial education and/or financial assets; vocational and/or business skills training interventions; and integrated interventions providing a combination of support services, including an economic component. The review synthesises evidence on the positive impact these interventions had, and identifies the gaps in our knowledge about which strategies are most effective. All three groups of interventions demonstrated the potential to improve girls' economic capabilities. However, significant evidence gaps remain and more research is needed to determine, for example, the optimal duration and intensity of programmes, the relationship between girls' economic empowerment and their vulnerability to violence and early marriage, and what is effective in certain regions and settings.
Keywords: 330